Acute toxicity of three herbicide formulations of Astyanax altiparanae (Characiformes, Characidae), an emerging neotropical fish model species - Rocha, Nathalia R. A. [UNESP]; Freato, Thiago A.; Filho, José T.; Barbosa, Admilson C.; Lázaro, Talita M.; Schade, Gabriel M.; Carvalho, Gabriella B.; Oliveira, Carlos A. F.; Senhorini, José A. [UNESP]; Yasui, George S. [UNESP]; Monzani, Paulo S. [UNESP] (Taylor & Francis, 2023)
Herbicides are used in agriculture to control harmful crop weeds, prevent algae proliferation, and enhance macrophyte growth. Herbicide contamination of water bodies might exert toxic effects on fish in different development stages. Sperm, embryos, and adults of Astyanax altiparanae were used as a model to examine the detrimental effects of the following herbicide formulations: Roundup Transorb® (glyphosate), Arsenal® NA (imazapyr), and Reglone® (diquat). The lethal concentration 50 (LC50) values for adults using glyphosate and imazapyr were 3.14 mg/L and 4.59 mg/L, respectively, while the LC50 was higher than 28 mg/L for diquat. For the initial stages of embryo development, LC50 values were 16.52 mg/L glyphosate, 9.33 mg/L imazapyr, and 1084 mg/L diquat. Inhibition of sperm motility was noted at 252 mg/L glyphosate, 137 mg/L imazapyr, and 11,300 mg/L diquat, with an average sperm viability of 12.5%, 73.2%, and 89.3%, respectively, compared to 87.5% detected to control. A.altiparanae exhibited different sensitivities to the herbicide formulations investigated in the developmental stages evaluated. Roundup Transorb® exposure was more toxic for adults, while Arsenal® NA was most harmful for early embryonic development and inhibited sperm motility. Reglone® demonstrated low toxicity for A.altiparanae compared to Roundup Transorb® and Arsenal® NA. A.altiparanae may be considered an emerging fish model for toxicological studies for the neotropical region due to its wide distribution and biological characteristics.
Keywords: and LC50; Astyanax altiparanae; diquat; Glyphosate; imazapyr